Evaluation of the diuretic and urinary electrolyte effects of methanolic extract of Peganum harmala L. in Wistar albino rats - Al-Saikhan, Fahad I.; Ansari, Mohd N. (Saudi journal of biological sciences, 2016)
The use of traditional medicines as a diuretic agent has been increasing in recent years. The diuretic activity of a number of plant extracts used as diuretic agents in ethnomedicine has been confirmed in experimental animals. However, despite the widespread use of Peganum harmala in traditional medicine, there is a paucity of data supporting its use as a diuretic agent. Therefore, the present study aimed to envisage the true effect and magnitude of diuresis of methanolic extract of P. harmala (MEPH) in comparison with a well-known diuretic drug furosemide using Wistar albino rats. MEPH was administered orally in three different doses (150, 300 and 450mg/kg) to experimentally dehydrated rats. Furosemide (10mg/kg orally) was used as a reference drug. The diuretic effect of the MEPH was evaluated by measuring urine volume, urine pH, urinary electrolyte levels, natriuretic and saliuretic effects. The urine volume (in mL) measured at 5h and 24h and electrolyte excretion (Na+, K+, and Cl−) at 24h duration were measured. The urine output and urinary electrolyte excretion were found to be significantly higher in rats treated with MEPH as compared to normal rats in a dose dependent manner (P<0.05). The results of our study were comparable to furosemide drug. Based on observed results, we can recommend that P. harmala may be an effective diuretic, however, toxicity studies should be conducted before administration.